Eficiencia del Sector Bancario en el Ecuador - Carrillo Bravo, Josue David (2024)
ABSTRACT: The study focuses on the efficiency of the Ecuadorian banking sector between the period 2010 and 2022, concentrating on its economic relevance and its impact on the management of financial resources. The importance of addressing challenges such as instability and insolvency through more effective regulation and rigorous supervision is highlighted. Two models are explored, Data Envelopment Analysis (DEA) and the Free Disposition Helmet (FDH), to measure the technical efficiency of the sector, using input variables (deposits, administrative expenses and social capital) and outputs (loans, investments and profit before taxes) all in thousands of dollars, divided into two groups; large and medium-sized banks, which will provide crucial information about the country's economic development and recognize the importance of financial decision-making and its role in the national economy. The results showed notable efficiency in banking operations during the period studied, with optimization of resources, technological innovation, and a wide range of services offered. Regulatory policies played a crucial role in strengthening and promoting the sector's solvency. Medium-sized banks showed lower levels of efficiency due to a difference in assets and higher expenses, while large banks maintained more consistent efficiency, so the comparison between the DEA and FHD methods revealed significant differences in the results, while the DEA provides a structured and comparative evaluation, the FDH offers a more adaptive and accurate view of Ecuadorian banking efficiency Keywords: Banking sector, efficiency, Ecuadorian economy, Data Envelopment Analysis (DEA), Free Disposition Hull (FDH) and financial production.